The Impact of Social Networking Sites’ Usage on the Academic Performance of University Students of Lahore, Pakistan - Waqas, Ali; Afzal, Muhammad; Zaman, Fakhar; Sabir, Muhammad (International Journal of Social Sciences and Management, 2016)
Social networking sites are more common to the young generation worldwide. Pakistan’s major population is comprised of young generation. Thus, usage of social networking sites has become the trend among the youth of Pakistan which has strong effect on the student’s performance and habits. Thus, this study aims to examine the impact of social network usage on the university student’s academic performance of Lahore, Pakistan. Cross sectional survey technique has used in the current study. The self-administered questionnaire distributed to the 260 students of four universities of Lahore through convenient random sampling. Descriptive analysis was used to analyze the data while Chi-square (X2) analysis has performed to test the research hypotheses. The findings of the current study show that the university students of Lahore, Pakistan are using different social networking sites which has negative effect on the student’s academic performance and habits. Int. J. Soc. Sc. Manage. Vol. 3, Issue-4: 267-276